A review on sensing and catalytic activity of nano-catalyst for synthesis of one-step ammonia and urea: Challenges and perspectives - Qureshi, S. (Elsevier Ltd, 2022)
One of the most significant chemical operations in the past century was the Haber-Bosch catalytic synthesis of ammonia, a fertilizer vital to human life. Many catalysts are developed for effective route of ammonia synthesis. The major challenges are to reduce temperature and pressure of process and to improve conversion of reactants produce green ammonia. The present review, briefly discusses the evolution of ammonia synthesis and current advances in nanocatalyst development. There are promising new ammonia synthesis catalysts of different morphology as well as magnetic nanoparticles and nanowires that could replace conventional Fused-Fe and Promoted-Ru catalysts in existing ammonia synthesis plants. These magnetic nanocatalyst could be basis for the production of magnetically induced one-step green ammonia and urea synthesis processes in future. Â© 2021